Model Pengembangan Keamanan Data dengan Algoritma ROT 13 Extended Vernam Cipher dan Stream Cipher - Yanuar Chris Milian; Wiwin Sulistyo (KITA Institute, 2023)
This research focuses on the importance of data security in maintaining confidentiality, particularly for sensitive and critical information that should only be accessed by certain parties. Cryptography is a mathematical method used to secure data. Several methods are available, including ROT13, Vernam Cipher, and Stream Cipher. This study combines these three methods to achieve a higher level of data security. The analysis shows that the combination of these algorithms results in a stronger and more complex encryption process than using a single method. The process involves encrypting plaintext using ROT13, followed by encrypting the result using Vernam Cipher with an inputted key, and then encrypting the output again using Stream Cipher. The advantages of this combination model include enhanced data security, as demonstrated by the three-stage encryption and decryption process.